2019
DOI: 10.1098/rsos.190967
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vessel noise on the communication network of humpback whales

Abstract: Humpback whales rely on acoustic communication to mediate social interactions. The distance to which these social signals propagate from the signaller defines its communication space, and therefore communication network (number of potential receivers). As humpback whales migrate along populated coastlines, they are likely to encounter noise from vessel traffic which will mask their social signals. Since no empirical data exist on baleen whale hearing, the consequences of this are usually assumed, being the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Some sound units of this are repeated and organized in the same order in the reproduction phrase. The humpback whale sounds are typical of those used in social and foraging activities [57].…”
Section: Humpback Whalesmentioning
confidence: 99%
“…Some sound units of this are repeated and organized in the same order in the reproduction phrase. The humpback whale sounds are typical of those used in social and foraging activities [57].…”
Section: Humpback Whalesmentioning
confidence: 99%
“…Despite overall similarities in the spectral content of vessel and wind noise, wind-generated noise is homogeneous over broad areas, while vessel noise is produced by a (moving) point source. A possible explanation for the lack of a Lombard response to increasing level of vessel noise in humpback whales was mentioned by Dunlop (2016a), and later further discussed by Dunlop (2019), when studying the effect of vessel noise on the social sounds of this species. The author suggested that humpback whales may be responding to the presence of vessels instead of noise; and that vessels may be perceived as a threat.…”
Section: Coping With Vessel Noisementioning
confidence: 96%
“…By comparing interactions observed in the presence and absence of the noise vessel, we could assess the effect of this type of noise on the receivers of the song. As mentioned above, if the response of the receivers to the song playback is the same in the presence or absence of vessel noise, then the whales may be using spatial masking release (Dunlop, 2019). This hypothesis may be further tested by changing the relative bearing of the two vessels in relationship to the receivers.…”
Section: Test Alternative Coping Mechanisms To Deal With Noisementioning
confidence: 99%
See 2 more Smart Citations